The history and investigative powers of congressional investigations: fundamental configuration and relevant aspects of the institute in Brazil (Research, Society and Development, 2022)
The present work aims to understand the legal nature of the Parliamentary Inquiry Commissions, in addition to indicating their various limits, given the considerable importance of the institute in the maintenance of the Democratic State of Law. Throughout the text, the institute's relationship with the theory of the tripartition of powers is developed, its origin in English law, the configuration of the institute throughout the various Brazilian constitutional laws, the requirements for its establishment, in addition to the limits applied to its investigative instructive powers. Furthermore, the method of hypothetical-deductive approach and auxiliary historical-comparative methods, applied research and qualitative exploratory analysis were used. The purpose of the research is a formative evaluation with a bibliographic research technique and a case study. Finally, it is concluded that the institute is essential for the maintenance of the checks and balances regime, but it needs a more detailed legislative treatment, in order to prevent possible usurpations of powers or deviations of purpose, especially with regard to the law silence, management of breach of confidentiality, handling of illicit evidence and the use of plea bargains.